Power optimization control of VSC-HVDC system for electromechanical oscillation suppression and grid frequency control - Bi, Chaohao; Wu, Jiaqi; Qian, Yang; Luo, Xin; Xie, Jianxiang; Shi, Jianquan; Luo, Fang (Frontiers in Energy Research, 2022)
The VSC-HVDC system usually adopts additional damping control and inertia control strategies to quickly and independently adjust the active and reactive power of the VSC, in order to improve the frequency stability and suppress the electromechanical oscillations of the synchronous generator grid. This paper first analyzes the effect of the PD controller parameter on the output power of the VSC inverter station. The study shows that when the PD controller parameter is increased to the limit value, the VSC will operate in the rapid power compensation (RPC) mode. Namely, according to the positive or negative polarities of the rotor speed deviation and the grid frequency deviation, the active and reactive power limits are used as the reference to rapidly control the output power of the VSC, thereby minimizing the system’s unbalanced active power, the rotor oscillation, and the frequency fluctuation. To this end, this paper proposes a coordinated active/reactive power control strategy for the VSC-HVDC system based on the RPC mode to suppress the grid electromechanical and frequency oscillations. The RPC mode enables the VSC to quickly release/absorb power, in order to compensate for system’s required power shortage or suppress excess power. When the speed deviation, the frequency deviation, and their rates of change meet the requirements, the damping control is used to make the VSC exit the RPC mode and further enhance the ability of the VSC-HVDC system. Simulation results prove the effectiveness of the proposed strategy.